2019
DOI: 10.3390/pharmaceutics11100523
|View full text |Cite
|
Sign up to set email alerts
|

Spray Drying of a Subcritical Extract Using Marrubium vulgare as a Method of Choice for Obtaining High Quality Powder

Abstract: White horehound (Marrubium vulgare L.), is a grey-leaved perennial herb, belonging to Lamiaceae family, distributed in Eurasia and northern Africa. Despite the fact that M. vulgare has been used since ancient times in treating diverse diseases, it is only in the last decade or so that scientists have been able to lay the foundation for its potential pharmacological actions from the results observed through the prism of ethnopharmacological use of this species. The novelty of this study was that subcritical wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 53 publications
(70 reference statements)
2
16
0
Order By: Relevance
“…Furthermore, recoveries of both phenolic acids and flavonoids were distinctly higher when 10% maltodextrin was added as a carrier, which suggested that maltodextrin addition protects bioactive compounds from thermal degradation. This is particularly emphasized in the case of rutin content, which was 4-fold higher when a carrier was included [ 32 ]. It is reported that marrubiin, as the main active compound isolated from M. vulgare , can be successfully separated from complex mixtures by chitin, which is an abundant natural polymer [ 52 ].…”
Section: Optimization Purification Processmentioning
confidence: 99%
“…Furthermore, recoveries of both phenolic acids and flavonoids were distinctly higher when 10% maltodextrin was added as a carrier, which suggested that maltodextrin addition protects bioactive compounds from thermal degradation. This is particularly emphasized in the case of rutin content, which was 4-fold higher when a carrier was included [ 32 ]. It is reported that marrubiin, as the main active compound isolated from M. vulgare , can be successfully separated from complex mixtures by chitin, which is an abundant natural polymer [ 52 ].…”
Section: Optimization Purification Processmentioning
confidence: 99%
“…Marrubium vulgare contains polyphenols and flavonoids that produced hypoglycemic effects, reduced cholesterol, triglyceride, and oxidative stress. Some flavonoids, such as apigenin, competitively inhibit the binding of flunitrazpam, thereby reduce the secretion of LH [44,70,71]. Also, the β-testosterone in the extract of Marrubium vulgare reduces LH.…”
Section: Licoricementioning
confidence: 99%
“…β-sitosterol reduces estradiol levels by decreasing aromatase enzyme activity, thereby preventing conversion testosterone to estrogen. Also, apigenin and ursolic acid of white horehound extract, inhibit cytochrome P450 and inhibit the conversion of cholesterol to pregnenolone, and thus reduce the synthesis of steroid hormones such as progesterone [70,71].…”
Section: Licoricementioning
confidence: 99%
“…The powder form of extracts ensures easy manipulation and shipping, lower storage and transportation costs, and easier standardization [14]. A lot of studies were conducted on the microencapsulation of different phytochemicals [15][16][17], but there is no published data on the stabilization of phytochemical compounds extracted from CBS by subcritical water.…”
Section: Introductionmentioning
confidence: 99%